PENGARUH PEMBERIAN PANGAN FORTIFIKASI ZAT MULTI GIZI MIKRO PADA IBU HAMIL TERHADAP PERTUMBUHAN LINIER, TINGGI LUTUT DAN STATUS ANEMIA BAYI - Saragih, Bernatal; Syarief, Hidayat; Riyadi, Hadi; Nasoetion, Amini (GIZI INDONESIA, 2007)
EFFECT OF MULTI MICRONUTRIENTS FORTIFIED SUPPLEMENTARY FOOD IN PREGNANT WOMEN ON LINEAR GROWTH, KNEE HEIGHT AND ANEMIA STATUS OF INFANTSLike in many developing countries, macro and micro nutritional deficiencies are the seriousproblem, especially for Indonesian pregnant women and young age children. Early nutritionalintervention strategy through supplementary fortified foods for pregnant women is one ofalternative nutritional improvement interventions for the next generation. The objective of this study is to analize the impact of multi micronutrients fortified supplementaryfood in pregnant mothers on linear growth, knee height and anemia status of infants. This studywas conducted in three sub-districts of Bogor Distritcs namely: Leuwiliang, Leuwisadeng andCiampea. This prospective cohort study follow up 120 infants. The total of infants has beenfollowed up was 120. From 120 born infants, 40 infants were selected as a fortified group in whichtheir mothers during pregnancy received fortified food (consists of vermicelli, milk and biscuit withmulti-nutrients i.e. iron, iodine, zinc, folic acid, vitamin C and vitamin A), 40 infants as unfortifiedgroups in which their mothers was received non fortified foods, and 40 infants as control groups(their mothers did not receive any experiment food). Data analyzed using SPSS 13.0. Z-scorewere calculated for the length-for-age (HAZ) of WHO 2006 growth reference.The result of study showed that multi micronutrients fortified supplementary food for pregnantmothers had significant effect on infants linear growth which was 2.18 cm taller compared tocontrol group and 1.53 cm taller compared to unfortified group. The mean of liniear growth andHAZ fortified group up to 6 months infants was better than unfortified and control. Earliercomplementary food intoduction were associated with the decrease of infants’ linear growth andHAZ. Stunting (5.0%) was found at two months of infants’ age in control group. Fortified foodsupplementation for pregnant women had significant effect on infant knee height gain. Infant kneeheight (< 14.248 cm) at 6 months was categorized as stunting. Multi micronutrients fortifiedsupplementary food in pregnant mother had an retention effect of decreased infants Hb at up to 6months.Keywords: Multi micronutrients, pregnancy, infant, breast feeding, linear growth, knee height, hemoglobin